Effect of Natural Feed Changing Time on Growth and Survival of Betok Fish Larvae (Anabas testudineus Bloch) - Muhammad Hidayat; Netti Aryani; Nuraini Nuraini (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The research was conducted in february to April 2021 in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this study was to know the effect of changing Artemia sp with MeM microdiet feed and to find out the best feed change time for growth and survival of Climbing perchlarvae.The method used in this study is an experimental method with a one-factor Completely Randomized Design (CRD) with seven treatments and 3 replications. The treatments were P0 (Artemia sp for 40 days), P1 (Artemia sp for 32 days and 8 days MeM pellets, P2 (Artemia sp for 26 days and MeM pellets for 14 days), P3 (Artemia sp for 20 days and MeM pellets for 20 days). ), P4 (Artemia sp for 14 days and MeM pellets for 26 days), P5 (Artemia sp for 8 days and MeM pellets for 32 days), P6 (MeM pellets for 40 days). in this study were larvae aged 5 days, which came from semi-natural spawning with ovaprim injection dose for males 0.5 ml/kg body weight and females with a dose of 0.5 ml/kg body weight.The results showed that there was an effect of time replacement of Artemia nauplii with MeM microdiet feed. The time of alternation of Artemia nauplii with MeM microdiet diet after 20 days of age (P3) gave the best results on growth rates such as absolute weight growth, daily growth rate, and absolute length growth, as well as growth rate. at each of 0.8243 g, 14.6467%/ day, 3.7356 cm, and 95.67%, respectively